PENGEMBANGAN MEDIA PEMBELAJARAN LUDO BERBASIS TEAM GAMES TOURNAMENT (TGT) PADA MATERI PECAHAN - Tri Astika Yolanda; Elvi Mailani (Universitas Negeri Medan, 2023)
Abstract : Development of Ludo Learning Media Based on Team Games Tournament (TGT) on Fraction Material in Class V SD Negeri 112298 Aek Kanopan Labuhanbatu Utara. The purpose of this study is to produce a feasible, practical and effective team games tournament (TGT)-based ludo learning media for use in learning. This research and development was carried out using the 4D model (Define, Design, Development and Dessimination). The subjects in this study were fifth grade students at SD Negeri 112298 Aek Kanopan Labuhanbatu Utara. The data collection techniques used were observation, interviews, validation questionnaires, and tests. The results of this study indicate that the team games tournament (TGT)-based ludo learning media is very feasible and practical to use. This is evidenced by the results of the final assessment of all validators, with details from the material expert validator obtaining a percentage of 86.6%, from the media expert validator obtaining a percentage of 89%, then from practical experts obtaining a percentage of 92.5%. The three assessments are included in the